2005
DOI: 10.1017/s135824610505602x
|View full text |Cite
|
Sign up to set email alerts
|

Other Histories, Other Biologies

Abstract: When philosophers look to the history of biology, they most often ask about what happened, and how best to describe it. They ask, for instance, whether molecular genetics subsumed the Mendelian genetics preceding it, or whether these two sciences have main–tained rather messier relations. Here I wish to pose a question as much about what did not happen as what did. My concern is with the strength of the links between our biological science—our biology—and the particular history which brought that science into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Such a supposition is, of 8 See Inkpen and Turner (2012). 9 See, e.g., Radick (2005), p. 24 and Hacking (1999), p. 80 and (2000), p. 70. 10 See, e.g., Keller (1985Keller ( , 1995.…”
Section: The Pusu Objection and An Impassementioning
confidence: 99%
“…Such a supposition is, of 8 See Inkpen and Turner (2012). 9 See, e.g., Radick (2005), p. 24 and Hacking (1999), p. 80 and (2000), p. 70. 10 See, e.g., Keller (1985Keller ( , 1995.…”
Section: The Pusu Objection and An Impassementioning
confidence: 99%
“…It is often believed that case studies from the history of science warrant specific philosophical views on the contingency issue. Most arguments in favor of contingentist interpretations of science have been put forward on the basis of historical accounts of past scientific developments (Bowler, 2008;Chang, 2012, 14e65;Collins, 1985, 79e111;Cushing, 1994;Pickering, 1984;Radick, 2003Radick, , 2005. And inevitabilists too cite historical material to underpin their views (Weinberg, 1994, 236e37;Weinberg, 2001, 198e199;Franklin, 1990Franklin, , 1994Franklin, , 2008.…”
Section: The Challenge Of Decidabilitymentioning
confidence: 99%
“…Close attention to the particular, the local and the contingent became a hallmark of good historiographical writing. More recently, ventures in counterfactual history explored possible or plausible alternative scientific trajectories (Bowler, 2008;Chang, 2012, 43e50;Radick, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Jim Cushing, following in Forman’s footsteps, has attributed the dominance of the Copenhagen interpretation of quantum mechanics among physicists to historical contingency (Cushing, 1994). More recently, Gregory Radick has suggested that there was nothing inevitable about the ‘discovery’ of genes and explored alternative paths that biology might have taken (Radick, 2005).…”
Section: Commentary 03
Causes and Contingencies In The History Of Scimentioning
confidence: 99%